Phasic electrical remodeling of ventricular myocardium affects arrhythmogenesis in rats with type 1 diabetes mellitus - Sedyakina, Ekaterina N; Tsvetkova, Alena S; Gonotkov, Mikhail A; Durkina, Alexandra V; Bernikova, Olesya G; Azarov, Jan E; Ovechkin, Alexey O (Journal of electrocardiology, 2025)
BACKGROUND: Diabetes mellitus (DM) causes myocardial electrical remodeling and promotes ventricular tachycardia and/or fibrillation (VT/VF). However, experimental studies have been frequently unsuccessful in developing a DM model with the expected high level of arrhythmic outcomes. The present study aims at evaluating cardiac electrophysiological properties in the rats with different Type 1 DM (T1DM) durations and identifying an electrophysiological phenotype associated with the high incidence of VT/VF. METHODS: The experiments were performed in 109 male Wistar rats (6-10 weeks old), subdivided into the groups of control, 4-weeks and 8-weeks T1DM (streptozotocin model). The animals were studied with epicardial electrophysiological mapping, whole-cell patch-clamp and histological examination. The VT/VF susceptibility was tested in ischemia/reperfusion induced in the anesthetized animals. RESULTS: In the 4-weeks T1DM group, we observed the increase in the incidence of reperfusion VT/VF, collagen deposition and dispersion of repolarization, slowed longitudinal and transverse conduction velocity, prolonged action potential duration, increased INa and ICaL currents, nonchanged Ito and IK1 currents. In the 8-weeks T1DM group, the VT/VF incidence, dispersion of repolarization, INa and Ito currents decreased. Other parameters persisted unchanged as compared to the 4-weeks T1DM group. CONCLUSIONS: Relatively early (4 weeks) diabetic electrical remodeling was proarrhythmic and included augmentation of sodium and calcium currents in the presence of fibrosis and slowed conduction and increased dispersion of repolarization. An unexpected finding was that diabetic arrhythmogenesis was associated with the increase in depolarizing transmembrane currents. Further research is warranted to elucidate molecular mechanisms and test the potential for the control of observed changes.
Keywords: Diabetes Mellitus, Experimental; Ventricular Remodeling; experimentální diabetes mellitus; modely nemocí na zvířatech; akční potenciály; krysa rodu Rattus; zvířata; Action Potentials; potkani Wistar; fibrilace komor; diabetes mellitus 1. typu; Rats, Wistar; Male; Ventricular Fibrillation; Rats; komorová tachykardie; Animals; mužské pohlaví; Disease Models, Animal; remodelace komor; Diabetes Mellitus, Type 1; Tachycardia, Ventricular